Penggunaan Indeks Harga dalam Menganalisis Pergerakan Harga Komoditas Pangan di Indonesia Periode 2017-2023 - Melindah, Devi; Wulan, Elis Ratna (CV. Kalimasada Group, 2024)
This study aims to explore the effectiveness of the use of index prices in analyzing commodity price movements over a certain period. Through historical analysis and statistical methods, this study aims to find out the extent to which index numbers can be used as an analysis tool in the commodity market. The methods used include the Laspeyres, Paasche, and Ideal Fisher price index formulas. The results of this study show that by using the Laspeyres, Paasche, and Ideal Fisher index calculation method, it can be concluded that food commodity prices have increased significantly. This increase in prices indicates inflation in the food sector, which requires an inflation control strategy to maintain price stability. Wage adjustments and social policies must take into account these increases to protect people's purchasing power. In addition, policies that support food production and distribution need to be improved to stabilize prices. The increase in food prices in Indonesia during this period shows the need for serious attention to ensure price stability and national food security.